Concluding Notes - Anumba, C.; Wang, Xiangyu (Wiley-Blackwell, 2012)
This chapter concludes the book and draws together a number of the threads running through the various chapters. It starts with a brief summary of the contents of the book, restates the main benefits of mobile and pervasive computing firms in the architecture, engineering, construction and facilities management (AEC/FM) sector. It also highlights a number of considerations in the effective utilization of mobile and pervasive computing in this industry sector. The last section of the chapter explores some of the future directions in mobile and pervasive computing in the construction industry. © 2012 John Wiley & Sons Ltd.